2018
DOI: 10.1083/jcb.201802023
|View full text |Cite
|
Sign up to set email alerts
|

A NUMB–EFA6B–ARF6 recycling route controls apically restricted cell protrusions and mesenchymal motility

Abstract: The endocytic protein NUMB has been implicated in the control of various polarized cellular processes, including the acquisition of mesenchymal migratory traits through molecular mechanisms that have only been partially defined. Here, we report that NUMB is a negative regulator of a specialized set of understudied, apically restricted, actin-based protrusions, the circular dorsal ruffles (CDRs), induced by either PDGF or HGF stimulation. Through its PTB domain, NUMB binds directly to an N-terminal NPLF motif o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 84 publications
2
18
0
Order By: Relevance
“…Thus, EFA6B depletion in both luminal and basal cells induces EMT and stimulates collective invasion. In agreement with our results, it was recently reported that the endocytic protein NUMB inhibits the acquisition of migratory and invasive properties by activating EFA6B/ARF6 in response to growth factors 36 .…”
Section: Emtsupporting
confidence: 94%
“…Thus, EFA6B depletion in both luminal and basal cells induces EMT and stimulates collective invasion. In agreement with our results, it was recently reported that the endocytic protein NUMB inhibits the acquisition of migratory and invasive properties by activating EFA6B/ARF6 in response to growth factors 36 .…”
Section: Emtsupporting
confidence: 94%
“…While this finding is well in line with a function of Numb as endocytic adaptor, its impact on Notch signaling appears to be more complex since Numb was also reported to influence the postendocytic trafficking [269] and degradation of Notch [33] as well as its ligand Dll4 [270]. In fact, Numb has been shown to interact not only with endocytic proteins and cargo, but also with components of the recycling machinery such as EFA6B-Arf6 [271] and EHD proteins [272] and with Ubiquitin ligases [33], and is implicated in the sorting of proteins such as N-cadherin [273] and APP [274].…”
Section: Insights Into Numb Function From D Melanogastermentioning
confidence: 63%
“…Finally, we calculated a cell elongation index (the ratio between the major and minor axis of cell, Fig EV7D) which directly correlates with mesenchymal migration, a specific mode of cell locomotion through the ECM, associated with CDR-dependent matrix invasion (Hoon et al, 2012;Suetsugu et al, 2003;Zobel et al, 2018). We found that the cell elongation index of GAS6-stimulated cells forming CDRs was significantly higher in comparison to nonstimulated cells ( Fig 6I, Fig EV7D).…”
Section: Gas6-axl-induced Cdrs Are Involved In Fa Disassemblymentioning
confidence: 92%